Criminal Law Interpretation of Crime Motives Influenced by Social Media Algorithms - Mulyana, Yusep (PT. Hafasy Dwi Nawasena, 2025)
The development of social media algorithms has significantly transformed how individuals form preferences, emotions, and behavior through engagement based content curation. In criminal law, this phenomenon raises new issues when algorithms are alleged to influence criminal motives, including hate based crimes, violence, and radicalization. Indonesian criminal law traditionally treats motive as an internal factor relevant to sentencing, yet it has not accommodated algorithmic influence as an external factor shaping criminal motives. This study aims to analyze the interpretation of criminal law regarding algorithm influenced criminal motives and to examine the implications of normative ambiguity for determining mens rea and criminal responsibility. Employing a normative juridical method with statutory, conceptual, and case approaches, the study finds that ambiguity in criminal norms regarding algorithmic influence leads to inconsistent judicial reasoning and risks of disproportionate sentencing. The study concludes that adaptive criminal law interpretation is required to address technological developments while preserving individual criminal responsibility and human rights protection.